2020
DOI: 10.1891/vv-d-18-00058
|View full text |Cite
|
Sign up to set email alerts
|

Dark Triad Personality Traits in Cyber Aggression Among College Students

Abstract: Despite evidence supporting the importance of cyber aggression among early adolescents (Hinduja & Patchin, 2015), we know less about its correlates among college students. The present study examined the relationships of Dark Triad personality traits to cyber aggression in a college student sample (N = 297). Machiavellian, narcissistic (both grandiose and vulnerable forms), and psychopathic traits positively related to cyber aggression perpetration. A hierarchical multiple regression including gender, age, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 40 publications
0
4
1
1
Order By: Relevance
“…They are related to risky sexual behavior (Fulton et al, 2010), overt and relational aggression (Schmeelk et al, 2008; Van Baardewijk et al, 2009), violent criminal history (Campbell et al, 2004), bullying (Antoniadou et al, 2016; Ragatz et al, 2011), and differences in moral foundations (e.g., harm/care, in-group loyalty; Mededovic & Petrović, 2016). Several studies have found that the total scores from various measures of psychopathic traits are positively related to cyber aggression among emerging adults (Craker & March, 2016; Goodboy & Martin, 2015; Kokkinos et al, 2014; Nocera & Dahlen, 2020); however, few used psychometrically sound measures of cyber aggression appropriate for emerging adults, and many used brief measures of psychopathy, which may not adequately capture the construct. Thus, we expected that psychopathic traits would be positively associated with cyber aggression perpetration.…”
Section: Predictors Of Cyber Aggressionmentioning
confidence: 99%
“…They are related to risky sexual behavior (Fulton et al, 2010), overt and relational aggression (Schmeelk et al, 2008; Van Baardewijk et al, 2009), violent criminal history (Campbell et al, 2004), bullying (Antoniadou et al, 2016; Ragatz et al, 2011), and differences in moral foundations (e.g., harm/care, in-group loyalty; Mededovic & Petrović, 2016). Several studies have found that the total scores from various measures of psychopathic traits are positively related to cyber aggression among emerging adults (Craker & March, 2016; Goodboy & Martin, 2015; Kokkinos et al, 2014; Nocera & Dahlen, 2020); however, few used psychometrically sound measures of cyber aggression appropriate for emerging adults, and many used brief measures of psychopathy, which may not adequately capture the construct. Thus, we expected that psychopathic traits would be positively associated with cyber aggression perpetration.…”
Section: Predictors Of Cyber Aggressionmentioning
confidence: 99%
“…Some researcher found that Machiavellianism (Kircaburun et al, 2018) and grandiose manipulative trait (a sub construct of psychopathy; Ciucci et al, 2014;Orue et al, 2016) better predict CA among men, whereas others indicated that callous-unemotional trait (another sub construct of psychopathy; Orue et al, 2016) and psychopathy (Zhu and Jin, 2021) was more strongly related to aggression in girls. However, other studies shown that gender could not moderate these relationship (Nocera and Dahlen, 2020;Wright et al, 2020). Thus, it becomes essential for examining the gender differences between these variables.…”
Section: Moderating Effect Of Gendermentioning
confidence: 97%
“…Consequently, empirical and meta-analytical studies have found that males consistently reported higher scores on dark triad personality ( Jones and Weiser, 2014 ; Muris et al, 2017 ). In addition, studies on CA indicated that women are prone to engage in relational and indirect CA, while men engage in more direct and physical CA ( Carbone-Lopez et al, 2010 ; Nocera and Dahlen, 2020 ). Moreover, it might be that males are more prone to involvement in cyber aggressive behaviors than females, because of their higher levels of dark personality features.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…Por último, la psicopatía fue definida como un conjunto de tendencias antisociales como impulsividad, falta de remordimientos, problemas para establecer vínculos emocionales, entre otros (Cleckley, 1941;Paulhus & Williams, 2002). Estos tres rasgos, independientes pero relacionados entre sí (Furnham et al, 2013;Muris et al, 2017), han mostrado asociación con distintos tipos de conductas desadaptativas como acoso laboral (Fernández-del-Río et al, 2021), bullying (Van Geel et al, 2017), adicciones comportamentales (Demircioğlu & Köse, 2021;Tang et al, 2020) y diferentes conductas agresivas y violentas (Barlett, 2016;Jones & Neria, 2015;Nocera & Dahlen, 2020). A pesar de la numerosa literatura dedicada en los últimos años a este concepto, hay pocos trabajos que hayan estudiado la asociación de la Tríada Oscura con la conducción agresiva (Ball et al, 2018;Burtăverde et al, 2016), encontrándose que los factores de personalidad de la Tríada Oscura se relacionan y predicen diversos aspectos de la conducción agresiva.…”
Section: Introductionunclassified